RESEARCH ON THE TECHNOLOGY OF MANUFACTURING A HEAT EXCHANGER ASSEMBLY USED AS A PART OF AN ELECTRICALLY DRIVEN CENTRIFUGAL AIR COMPRESSOR CCAE 15-300 (Nonconventional Technologies Review, 2021)
The paper presents the technical and operational characteristics of the heat exchanger assembly for a centrifugal air compressor CCAE 15-300. The structure and the component parts of the heat exchanger assembly are shown in the paper. The basic materials and the main characteristics of the components are described in the paper. The main objective of this article is represented by the description of the technology for manufacturing the components and the heat exchanger assembly by soft soldering with tin.
Keywords: soldering. heat exchanger assembly; manufacturing technology; centrifugal air compressor